2020
DOI: 10.1007/s10209-020-00777-w
|View full text |Cite|
|
Sign up to set email alerts
|

Can search result summaries enhance the web search efficiency and experiences of the visually impaired users?

Abstract: There are limited studies that are addressing the challenges of visually impaired (VI) users when viewing search results on a search engine interface by using a screen reader. This study investigates the effect of providing an overview of search results to VI users. We present a novel interactive search engine interface called InteractSE to support VI users during the results exploration stage in order to improve their interactive experience and web search efficiency. An overview of the search results is gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Satisfaction is one of the top usability variables for evaluating users' overall perception of information retrieval systems (Sbaffi and Zhao, 2020;Xie et al, 2018;Xu and Du, 2018). In the desktop environment, Aqle et al (2020) created a search interface for blind and visually impaired users with enhanced accessibility and usability functions and compared it with the Google interface. The result demonstrated that this interface reduced search time and increased user satisfaction over Google.…”
Section: Usability and Associated Design Factors In The Mobile Enviro...mentioning
confidence: 99%
“…Satisfaction is one of the top usability variables for evaluating users' overall perception of information retrieval systems (Sbaffi and Zhao, 2020;Xie et al, 2018;Xu and Du, 2018). In the desktop environment, Aqle et al (2020) created a search interface for blind and visually impaired users with enhanced accessibility and usability functions and compared it with the Google interface. The result demonstrated that this interface reduced search time and increased user satisfaction over Google.…”
Section: Usability and Associated Design Factors In The Mobile Enviro...mentioning
confidence: 99%
“…This search engine uses Formal Concept Analysis (FCA) to generate an overview of search results. InteractSE was evaluated with 16 users [23] and five HCI experts [24], showing a significant improvement in search efficiency and individual user experience for VI web users. The team continues to work on research projects related to accessibility and looking for aspiring scientists to join this journey.…”
Section: Research Experiencementioning
confidence: 99%
“…The authors [22,23] focused on the search engine as an essential component for searching information and proposed in their studies interactive tools to improve the interactive experience with the search engine. The authors [23] described a prototype search engine that provides a re-ranked set of search results.…”
Section:  Studies On Search Engine Componentmentioning
confidence: 99%